Utilizing Endoscopic Ultrasound-Guided Fine Needle Aspiration in Identifying Molecular Targets for Pancreatic Cancer - Ogbonna, Onyekachi Henry; Saif, Muhammad Wasif (JOP. Journal of the Pancreas, 2013)
Pancreatic cancer remains a devastating disease, with poor survival rates and high recurrence rates with current treatment regimens. Over the years we have come to understand the complex biology of this cancer, involving cross-talking signaling pathways that proffers resistance to current therapy. Several molecularly targeted agents remain in development. At the 2013 American Society of Clinical Oncology (ASCO) Annual Meeting, an abstract (#4051) was presented which explored using endoscopic ultrasound-guided fine needle aspiration of pancreatic cancer tissue to identify molecular targets, and argued for the feasibility of personalizing pancreatic cancer therapy based on the activated molecular pathways identified. We summarize their findings and discuss the possibility of utilizing this model to obtain a better understanding of pancreatic cancer at each stage of its metamorphosis and target therapy at these different levels. Image: Jaharis Family Center for Biomedical and Nutrition Sciences. Tufts University School of Medicine. Boston, MA, USA.